Effect of exercise on serum vitamin D and tissue vitamin D receptors in experimentally induced type 2 Diabetes Mellitus - Yosria E. Aly; Azza S. Abdou; Mona M. Rashad; Menatallah M. Nassef (Journal of Advanced Research, 2016)
This work aimed to study the effect of swimming exercise on serum vitamin D level and tissue vitamin D receptors in experimentally induced type 2 Diabetes Mellitus. Sixty adult male rats were divided into control and diabetic groups. Each was further subdivided into sedentary and exercised subgroups. Diabetes Mellitus was induced by a single intraperitoneal dose of streptozotocin (50 mg/kg) dissolved in cold 0.01 M citrate buffer (pH 4.5). The exercised subgroups underwent swimming for 60 min, 5 times a week for 4 weeks. Serum glucose, insulin, homeostasis model assessment of insulin resistance (HOMA-IR), lipids, vitamin D and tissue Vitamin D receptors (VDR) were evaluated. Significant increase in serum glucose, insulin, HOMA-IR, cholesterol, triglycerides, and low density lipoprotein (LDL) levels in sedentary diabetic rats was detected. On the other hand, high density lipoprotein (HDL), free fatty acids, serum vitamin D and pancreatic, adipose, and muscular VDR showed a significant decrease in the same group. It is evident that all these parameters were reversed by swimming exercise indicating its beneficial role in type 2 Diabetes. In diabetic groups; serum vitamin D was found to be correlated negatively with serum glucose, insulin, HOMA, cholesterol, triglycerides, and LDL and positively correlated with HDL and tissue VDR. In conclusion, Disturbed vitamin D is associated with metabolic impairments in sedentary diabetic rats. Moderate swimming exercise is beneficial in improving these consequences through modulation of vitamin D status. Future studies could be designed to investigate the effect of the combination of vitamin D intake with exercise in diabetic patients.